Glucose Metabolism Reprogramming of Vascular Endothelial Cells and Its Implication in Development of Atherosclerosis - Shiwen Luo; Liu Li; Huiqing Chen; Jingyue Wei; Dongmei Yang (Reviews in Cardiovascular Medicine)
Atherosclerosis (AS) is an important cause of morbidity and mortality in cardiovascular diseases such as coronary atherosclerotic heart disease and stroke. As the primary natural barrier between blood and the vessel wall, damage to vascular endothelial cells (VECs) is one of the initiating factors for the development of AS. VECs primarily use aerobic glycolysis for energy supply, but several diseases can cause altered glucose metabolism in VECs. Glucose metabolism reprogramming of VECs is the core event of AS, which is closely related to the development of AS. In this review, we review how glucose metabolism reprogramming of VECs promotes the development of AS by inducing VEC barrier dysfunction, autophagy, altering the inflammatory response, and proliferation of VECs, in the hopes of providing new ideas and discovering new targets for the prevention and treatment of AS.